Protecting youth from social media risks through information security practices and Islamic principles - Abdul Molok, Nurul Nuha; Kartiwi, Mira; S. Abd. Aziz, Madihah (2015)
The engagement of youth in social media such as Facebook, Twitter and Instagram is on the rise due to the advancement of mobile technology and the increasingly interconnected cyber world. Despite the benefits of social media to adolescents, young people are also exposed to security risks through these social sites. There have been alarming cases about youth and social media reported locally and internationally. Some of these cases involved cyberbullying, pornography, sexual victimization, addiction and becoming an accidental outlaw due to unthinkable postings on these sites. This conceptual paper explores such phenomenon that is affecting young people today and recommends ways to minimize the risks by educating them about information security practices in social media. Additionally, while other security studies refer to the Western theories and theoretical models, this paper refers to the Holy Quran and Hadith for conceptual analysis in order to propose safeguarding measures against the current phenomenon affecting today’s youth.